A Forgotten Pioneer in Sports Television: Phillies Jackpot Bowling (1959–1960). Issue 2 (3rd April 2019) - Hirshon, Nicholas
Abstract : Phillies Jackpot Bowling, a television series broadcast on NBC in 1959 and 1960, played a historic role in transforming the image of bowling and precipitating an era of unprecedented popularity for the game. Professional bowlers competed to roll six consecutive strikes in nine throws and hit a jackpot that reached tens of thousands of dollars. Winning contestants made more money in just a few minutes on the lanes than many baseball and football stars earned over an entire season. In an era when bowling was dismissed as the dull hobby of gamblers and drinkers, Phillies Jackpot Bowling cast the game as exciting and wholesome. The show also marked little-known chapters in the careers of its three famous hosts, Leo Durocher, Mel Allen, and Bud Palmer.